Assessing the Prevalence of Latent Tuberculosis among Health Care Providers in Zagazig City, Egypt Using Tuberculin Skin Test and QuantiFERON-TB Gold In-Tube Test - El-Sokkary, Rehab H; Abu-Taleb, Ashwak M; El-Seifi, Omnia S; Zidan, Haidy E; Mortada, Eman M; El-Hossary, Dalia; Farag, Salama E (Central European journal of public health, 2015)
AIM: Early detection of latent tuberculosis infection (LTBI) will prevent development of active TB among health care providers. The aim of the study was to assess the prevalence of LTBI among health care providers and compare the QuantiFERON-TB Gold In-Tube Test (QFT-GIT) and Tuberculin skin test in efforts to detect LTBI and to investigate possible associated risk factors of infection. METHODS: A cross sectional study was carried out during the period of 6 months in the Chest Hospital in Zagazig city and the Nephrology Unit at Zagazig University Hospitals in 132 randomly selected health care providers who were examined for LTBI by QFT-GIT and Tuberculin skin test and for the associated risk factors as well. RESULTS: The prevalence of LTBI identified by QFT-GIT and by Tuberculin skin test was 28.8% and 59.1%, respectively. Poor agreement was observed between the two tests (kappa=0.10). Working more than 10 years, being nurse, diabetic and smoker were risk factors significantly associated with LTBI (p<0.05). CONCLUSIONS: QFT-GIT is considered a useful tool in detecting LTBI cases, especially in a country where BCG vaccination is a national policy (as in Egypt). Duration of work, profession, diabetes and smoking are the risk factors for LTBI. Active surveillance and infection control measures are recommended to reduce the risk of LTBI.
Keywords: dospělí; Tuberculin Test; zdravotnický personál; Humans; tuberkulinový test; Prevalence; tuberculosis; QuantiFERON; Risk Factors; Surveys and Questionnaires; mužské pohlaví; tuberkulóza; Adult; Health Personnel; průzkumy a dotazníky; rizikové faktory; health care providers; Egypt; ženské pohlaví; Tuberculosis; lidé; prevalence; Tuberculin skin test; Male; Female